Effects of fermented unconventional protein feed on pig production in China - Sun, Haoxuan; Jiang, Zipeng; Chen, Zhimin; Liu, Guohua; Liu, Zexue (Frontiers in Veterinary Science, 2024)
Unconventional protein feeds, characterized by low nutritional value, high variability, and poor palatability, have limited their application in swine production. Fermentation technology holds the key to addressing these shortcomings. Given the ban on antibiotics in China, the inferior quality of imported pig breeds, and long-term dependence on imported soybean, the prospects for fermented unconventional protein feeds are promising. This paper delves into the common types of fermented unconventional protein feeds, factors influencing the fermentation process, the mechanisms by which they enhance swine health, and the challenges and prospects of fermented feeds, offering theoretical insights for the future development of the feed industry. 批注 [颢孙9]: Reply to Reviewer 2, I have listed the specific anti nutritional effects of commonly used protein resources and what other effects they may have on metabolism.